Hospital Length of Stay and Family Needs of Critically Ill Patients - Aliyyah Oktavia; Sri Rahayu (Indonesian Journal of Global Health Research, 2026)
The needs of families of patients treated in intensive care units with unstable conditions and uncertain lengths of stay often cause anxiety and increase the need for proximity, service assurance, support, information, dan comfort. The purpose of this study was to determine the relationship between hospital length of stay and family needs during intensive care. The method used was quantitative with a cross-sectional approach and purposive sampling technique. The study population consisted of family members of critically ill patients at Dr. Moewardi General Hospital in Surakarta, with 100 participants. The tool used was the Indonesian version of the Critical Care Family Needs Inventory (CCFNI) questionnaire with a Cronbach's alpha score of 0.97. Data analysis was performed using Spearman's rank correlation test to examine the relationship between hospital length of stay and family needs. The results showed a significant relationship between hospital length of stay and family needs in the dimensions of proximity (p = 0.003), service assurance (p = 0.029), and total family needs score (p = 0.035). No significant relationship was found between hospital length of stay and family needs in the dimensions of family support (p = 0.171), information (p = 0.131), and comfort (p = 0.401).